Royal jelly production with queens produced by single and double grafting in Africanized honeybee colonies - Pedro Rosa Santos; Tuan Henrique Smielevski de Souza; Diogo Francisco Rossoni; Vagner de Alencar Arnaut de Toledo (Acta Scientiarum: Animal Sciences, 2019)
The objective of this research was to evaluate royal jelly production from Africanized honeybee queens of different lineages (lineage selected for honey production, lineage selected for royal jelly production and unselected) produced by single and double grafting and to compare royal jelly production among their offspring. Data were tested by double factorial analysis of variance and the means were compared by Tukey test at 5%. The parameters evaluated were: queen weight at emergence, percentage of larvae acceptance in the upper and lower bars, royal jelly per cup (mg) and royal jelly per colony/collection (g). Queens selected for honey presented greater weight at emergence, while the unselected queens were the lightest. Double grafting was better than simple grafting, since the queens were born 2.38% heavier. There was no difference (p > 0.05) in relation to royal jelly production according to neither the lineage nor even comparing the method by which the queens were produced. The cost of labor to produce queens by double grafting was much higher, as by the simple grafting about 170% more queens were born. The potential of Africanized honeybees with adequate production management and favorable environmental conditions favors the production of royal jelly.